STRENGTHENING SPIRITUAL MENTALITY THROUGH POSITIVE AFFIRMATIONS: THE PREVENTIVE ROLE OF ISLAMIC EDUCATION TEACHERS IN ADDRESSING BULLYING - Firmansyah, Mokh. Iman; Surahman, Cucu; Faqihuddin, Achmad; Muflih, Abdillah; Nasrudin, Ega (Balai Penelitian dan Pengembangan Agama Makassar, 2024)
Bullying cases that occur among students in Indonesia today have become a problem that has become mainstream. Various official data information from the government reinforces this problem. This article aims to explore from the side of subjects who should play a preventive role in suppressing bullying cases among students as a form of their social competence responsibility. Phenomenological design was chosen to explore the experiences of 18 PAI teachers in elementary and junior high schools in providing positive affirmation to students. Two dimensions of positive affirmation were explored, namely self-acceptance and affirmation to prevent bullying through a closed questionnaire and then inductively content analyzed. The results of the study found that the involvement of the integration approach of spiritual values colored the positive affirmations given by PAI Teachers to encourage students to become individuals who are self-accepting, honest, positive, independent, and respectful of differences, strong mentality, self-confidence, and a safe school environment from bullying. This finding has implications and contributes to the importance of optimizing the role of subjects who have the opportunity to work preventively as part of their professionalism to reduce cases of bullying among students.